2020
DOI: 10.1016/j.molmet.2020.101048
|View full text |Cite
|
Sign up to set email alerts
|

Genetic loss of AMPK-glycogen binding destabilises AMPK and disrupts metabolism

Abstract: Objective Glycogen is a major energy reserve in liver and skeletal muscle. The master metabolic regulator AMP-activated protein kinase (AMPK) associates with glycogen via its regulatory β subunit carbohydrate-binding module (CBM). However, the physiological role of AMPK-glycogen binding in energy homeostasis has not been investigated in vivo . This study aimed to determine the physiological consequences of disrupting AMPK-glycogen interactions. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 46 publications
3
23
2
Order By: Relevance
“…AMPK b subunits contain an N terminus myristoylation site as well as a conserved carbohydrate binding module (CBM) that facilitates interactions with glycogen and an ag binding domain at the C terminus. Recent work has assessed the physiologic implications of AMPKb subunit CBM glycogen binding (Hoffman et al, 2020). These studies indicate a role for glycogen binding in stabilizing AMPK complex formation, AMPK activation, and lipid metabolism across multiple tissues.…”
Section: The Ampk Heterotrimeric Complex and Its Functional Implicationsmentioning
confidence: 99%
“…AMPK b subunits contain an N terminus myristoylation site as well as a conserved carbohydrate binding module (CBM) that facilitates interactions with glycogen and an ag binding domain at the C terminus. Recent work has assessed the physiologic implications of AMPKb subunit CBM glycogen binding (Hoffman et al, 2020). These studies indicate a role for glycogen binding in stabilizing AMPK complex formation, AMPK activation, and lipid metabolism across multiple tissues.…”
Section: The Ampk Heterotrimeric Complex and Its Functional Implicationsmentioning
confidence: 99%
“…We previously generated two isoform-specific AMPK β knock-in (KI) mouse models in which tryptophan residues critical for AMPK-glycogen binding were mutated in either the β1 (W100A) or β2 (W98A) subunit isoform [14]. We demonstrated that mice with a KI mutation to chronically disrupt glycogen-binding capacity in a single AMPK β subunit isoform predominately expressed in liver or skeletal muscle displayed reduced total AMPK content and kinase activity, which was associated with increased fat content in liver and skeletal muscle of β1 W100A and β2 W98A KI mice, respectively [14]. Additionally, β2 W98A KI mice displayed increased whole-body fat mass and impaired glucose handling [14].…”
Section: Introductionmentioning
confidence: 99%
“…The more traditional function of the CBM is to target AMPK to glycogen, an interaction we recently showed is critical for glucose handling and maximal exercise capacity [ 108 ]. The observed phenotype in this study was accompanied by a loss of total AMPK protein levels (~50–60% reduction), suggesting that the AMPK-glycogen interaction is important to stabilise certain pools of AMPK.…”
Section: Regulation By Phosphorylationmentioning
confidence: 99%